Subclinical vitamin A deficiency and associated factors among pregnant women in eastern Ethiopia - Roba, Kedir Teji; Asefa, Gemechu; Fite, Meseret Belete; Oumer, Abdu; Abdurahman, Dureti; Motuma, Aboma; Yilma, Abebayehu N.; Thompson, Gretchen; Brewis, Alexandra; Rosinger, Asher Y. (Frontiers in Nutrition, 2025)
IntroductionVitamin A is essential for maternal and child health and plays a key role in reducing maternal and child mortality rates. A need exists for more evidence on the prevalence and associated factors of Vitamin A deficiency (VAD) among pregnant women in rural, underserved areas, such as eastern Ethiopia, where many risk factors for VAD may be concentrated.MethodsA community-based cross-sectional study was conducted with 397 randomly selected pregnant women at the Haramaya University Demographic Health Surveillance sites. Data were collected through structured questionnaires, anthropometric measurements, blood serum samples, and other relevant household and individual-level information. Vitamin A deficiency (VAD) was defined as serum retinol levels <0.7 μmol/L, while marginal deficiency was defined as 0.70–1.05 μmol/L. Bivariable and multivariable logistic regression analyses were used to identify factors associated with VAD.ResultsApproximately 48.1% (43.1–53.1%) of pregnant women in eastern Ethiopia had subclinical vitamin A deficiency (VAD), with a mean serum retinol concentration of 0.82 (±0.02) μmol/L. Only 122 (30.7%) and 159 (40.1%) of the participants reported having adequately diversified diets and adequate food variety scores, respectively. The use of khat (a stimulant) (adjusted odds ratio [AOR] = 1.67; 95% CI: 1.08–2.57) and a lack of awareness regarding vitamin A-rich foods (AOR = 1.67; 95% CI: 1.04–2.68) were found to be positively associated with VAD. Khat chewing was responsible for approximately 40.1% of VAD cases. Additionally, greater educational attainment of the husband (AOR = 0.47; 95% CI: 0.25–0.90) was significantly protective against subclinical VAD.ConclusionAlmost half of the pregnant women in this eastern Ethiopian sample were found to have subclinical VAD, highlighting the need for nutritional education during antenatal care and community nutrition awareness campaigns by various stakeholders. Context-specific, targeted behavioral change communications are essential to improve dietary practices and healthcare utilization.